Peran Asuhan Kebidanan dalam Pencegahan Anemia di Trimester Kedua Kehamilan - Rosmiarti, Rosmiarti; Sagita, Sherly Deas (Ners Akademika, 2025)
Purpose: Providing comprehensive midwifery care for Mrs. “N” during pregnancy and delivering education about the anemia she is experiencing. Method: This case study used a descriptive observational method with a case study approach and progress notes in the form of SOAP. The subject was Mrs. “N” in her second trimester. Results: From the objective data obtained, Mrs. “N” was 20 weeks pregnant with mild anemia (Hb: 10.3 g/dl). She reported complaints such as dizziness and fatigue. Conclusions: A second-trimester pregnant woman with hemoglobin level of 10.3 g/dL is experiencing mild anemia, which poses a risk to fetal growth. Iron supplementation and nutritional education initiated during the second trimester are effective in increasing hemoglobin levels and preventing complications such as low birth weight and preterm labor. Limitations: This study was limited to a single case in one midwifery practice, which restricts the generalization of findings to a broader population. Laboratory follow-up to measure hemoglobin improvement after intervention was not conducted, so the long-term effect of education and supplementation could not be quantitatively evaluated. Contribution: This study provides practical insights into the implementation of comprehensive midwifery care using the SOAP approach for managing mild anemia in the second trimester. It emphasizes the importance of early iron supplementation and nutritional education as preventive measures to reduce pregnancy complications and improve maternal health outcomes.